Precipitation kinetics and mechanical properties of Mg–Y–Zn and Mg–Y–Ni alloys containing long-period stacking ordered (LPSO) structures - Amir Hossein Asadi; Parastoo Mahmoud Kalayeh; Hamed Mirzadeh; Mehdi Malekan; Massoud Emamy (Journal of Materials Research and Technology, 2023)
Microstructures, mechanical properties by tensile deformation, and precipitation kinetics during elevated-temperature homogenization/aging heat treatment of Mg95.5Y3Zn1.5 and Mg95.5Y3Ni1.5 (at.%) magnesium alloys were systematically compared in the present work. The microstructure of both alloys in the as-cast state consisted of α-Mg and 18R long-period stacking ordered (LPSO) phase. For peak aging at 473 K (maximum hardness), the 18R phase in Mg95.5Y3Zn1.5 alloy partly transformed to lamellar 14H-LPSO phase, and hence, the ultimate tensile strength (UTS) and total elongation increased from 160.6 MPa to 2.6% to 210.5 MPa and 8.5%, respectively. After similar aging treatment of the Mg95.5Y3Ni1.5 alloy, the βʹ-Mg7Y particles precipitated in the structure, and as a result of precipitation hardening effect, the UTS and total elongation increased from 143.4 MPa to 1.9% to 201.6 MPa and 9.2%, respectively. It was observed that the formation of LPSO and precipitating phases during thermomechanical processing might lead to an improvement of strength-ductility synergy, for which overaging at hot temperatures might also be considered for improving plasticity and work-hardening behavior. The investigation of the formation kinetics of 14H-LPSO in Mg95.5Y3Zn1.5 alloy and βʹ-Mg7Y in Mg95.5Y3Ni1.5 alloy based on the Johnson–Mehl–Avrami–Kolmogorov (JMAK) analysis led to the activation energy (Q) of 104 kJ/mol and 89 kJ/mol, respectively. The former is similar to that of the diffusion of zinc in the matrix and the latter is close to that for the diffusion of yttrium in the matrix. Accordingly, the present work can shed light on the phase transformations and strengthening mechanisms of high-strength LPSO-containing Mg alloys.